2020
DOI: 10.1096/fj.201902594rr
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial adaptations to exercise do not require Bcl2‐mediated autophagy but occur with BNIP3/Parkin activation

Abstract: Understanding the mechanisms regulating mitochondrial respiratory function and adaptations to metabolic challenges, such as exercise and high dietary fat, is necessary to promote skeletal muscle health and attenuate metabolic disease. Autophagy is a constitutively active degradation pathway that promotes mitochondrial turnover and transiently increases postexercise. Recent evidence indicates Bcl2 mediates exercise‐induced autophagy and skeletal muscle adaptions to training during high‐fat diet. We determined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 61 publications
3
47
1
Order By: Relevance
“…These data suggest that several days of lipid overload activates upstream mitophagy signals, which may be mediated through ROS production, as an initial signal for skeletal muscle mitochondria to adapt to dietary lipid. Our previous study demonstrated that compared with low-fat diet, mice consuming high-fat diet for 12 weeks had greater oxidative phosphorylation capacity specific for lipid substrates (6). In the current study, we demonstrated dynamic changes, specific to lipid respiration, within shorter time periods of 3 to 7 days.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…These data suggest that several days of lipid overload activates upstream mitophagy signals, which may be mediated through ROS production, as an initial signal for skeletal muscle mitochondria to adapt to dietary lipid. Our previous study demonstrated that compared with low-fat diet, mice consuming high-fat diet for 12 weeks had greater oxidative phosphorylation capacity specific for lipid substrates (6). In the current study, we demonstrated dynamic changes, specific to lipid respiration, within shorter time periods of 3 to 7 days.…”
Section: Discussionsupporting
confidence: 66%
“…Mice consumed either a low-fat diet (LFD; D12450J; Research Diets) or high-fat diet (HFD; D12492; Research Diets) ad libitum for 3 days and 7 days to measure acute effects on mitochondrial respiration. A third group consumed diets for 12 weeks to investigate long-term changes in protein abundance and signaling, but not respiration because long-term changes in respiration have been well-documented by our group ( 6 , 22 ). The percent kilocalories from total fat (from lard)/carbohydrate/protein was 10/70/20 for the LFD and 60/20/20 for the HFD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations